2018
DOI: 10.1590/1983-21252018v31n224rc
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Forage Cactus Fertigated With Domestic Sewage Effluent

Abstract: The northeastern semiarid region faces some of the droughts of the last centuries, resulting in serious reductions of agriculture yields. The water scarcity for agricultural requires rational use practices and reuse of water, such as use of domestic effluent sewage. Alternatively, the use of treated domestic sewage effluent utilizing for irrigation of forage species, such as the forage cactus, can be highlighted. In order to evaluate the effects of fertirrigation with treated sewage effluent on mineral nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
3
6
0
4
Order By: Relevance
“…Similar results were found by Lemos et al (2018) and Rocha et al (2017), in the first cultivation cycle. These authors observed that changes in prickly pear growth are slow in the initial stage of cultivation for all variables studied.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar results were found by Lemos et al (2018) and Rocha et al (2017), in the first cultivation cycle. These authors observed that changes in prickly pear growth are slow in the initial stage of cultivation for all variables studied.…”
Section: Resultssupporting
confidence: 89%
“…Similar results were obtained by Lemos et al (2018), who found a trend of greater thickness in cladodes of plants which received greater amount of water, at 75 DAP. Likewise, the measurements taken at 170 and 234 DASC demonstrated that the means of the treatments, either with or without significant differences, followed the same trend in which plants receiving a larger volume of water showed greater cladode thickness.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations